2006
DOI: 10.1021/np060237u
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Glycosides with Antioxidant Activity from the Stem Bark of Populus davidiana

Abstract: Phytochemical study on the EtOAc-soluble fraction of the stem bark of Populus davidiana resulted in the isolation of 10 phenolic glycosides (1-10), which were identified on the basis of physicochemical and spectroscopic analyses. Among these, three new compounds, populosides A-C (1-3), were determined to be 2-coumaroylmethyl-4-hydroxyphenyl-beta-D-glucopyranoside, 2-coumaroylmethylphenyl-beta-D-glucopyranoside, and 2-feruoylmethylphenyl-beta-D-glucopyranoside, respectively. Compounds 1-10 were tested for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 19 publications
1
23
0
1
Order By: Relevance
“…These findings indicate that a major component of the metabolites accumulated in the C3ЈH-14 transgenic line are ester-linked conjugates of p-coumaric acid. Liquid chromatography-mass spectrometry (LC-MS) evaluation of the same methanolic extracts revealed that the majority of the p-coumaric ester existed as 1-O-p-coumaroyl-␤-D-glucoside and in the form of phenylglucosides common to the phloem of the Salicaceae (16,17), including populoside, grandidentatin, and trichocarposide. Small amounts of p-coumaroyl shikimate (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that a major component of the metabolites accumulated in the C3ЈH-14 transgenic line are ester-linked conjugates of p-coumaric acid. Liquid chromatography-mass spectrometry (LC-MS) evaluation of the same methanolic extracts revealed that the majority of the p-coumaric ester existed as 1-O-p-coumaroyl-␤-D-glucoside and in the form of phenylglucosides common to the phloem of the Salicaceae (16,17), including populoside, grandidentatin, and trichocarposide. Small amounts of p-coumaroyl shikimate (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, down-regulation of C3ЈH led to a dramatic accumulation of several glucosides of p-coumaric acid, including O-p-coumaroyl-␤-D-glucoside and populoside, grandidentatin, and trichocarposide. The last three phenylglucosides have been shown to accumulate in the cortex and phloem of members of the family Salicaceae (16,17). An evaluation of the tissue-specific accumulation of these compounds revealed that the O-p-coumaroyl-␤-Dglucoside accumulates in the phloem, leaf tissue, and cambium; whereas populoside, grandidentatin, and trichocarposide are most highly detectable in phloem tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The high yield obtained in our studies for the isolation of the labdane diterpene 15 from L laricina bark (Pichette et al 2006c) could contribute to make this widespread species a good raw material for the production of bioactive labdane diterpenes from biomass. Phenolic compounds from Populus tremuloïdes buds Poplar trees are well known for their phenolic compounds content which includes flavonoids (Komoda 1989;Kurkin et al 1990), hydroxycinnamic acid derivatives (Greenaway et al 1988;Greenaway et al 1991; and phenolic glycosides (Ogawa et al 2006;Zhang et al 2006b). Interest in the chemical composition of the extractibles from the genus Populus is, in part, due to thousands of years old historical use of the resinous hive product Propolis.…”
Section: Labdane Diterpenes From Lorix Iaricinomentioning
confidence: 99%
“…However, it will be interesting to evaluate its potential as a dietary supplement..In fact, quinic acid ester and glucose ester of hydroxycinnamic acid structurally related to compound 27 are well known dietary phenolic compounds found in many fruits and vegetables (Winter et Herrmann 1986). Moreover, chlorogenic acid (28), the most common ester of hydroxycinnamic acid possesses antioxidant properties (Tsychiya et al 1996;Lafay et al 2006) that have been correlated with the prevention of different cancers Zhang et al 2006b;Ghedira et al 2009) as well as cardiovascular diseases (Suzuki et al 2002;Lafay et al 2006). Evaluation of the antioxidant activity of compound 27 is currently progressing in our laboratory to assess its potential as a dietary supplement from the buds of P. tremulo'ides.…”
Section: Labdane Diterpenes From Lorix Iaricinomentioning
confidence: 99%
See 1 more Smart Citation